Evaluación de diferentes niveles de inclusión de maralfalfa (Pennisetum spp.) en dietas para cuyes sobre la integridad de la mucosa intestinal - Febres López, Dayanna Karolina (2023)
In the present study, the effect of the inclusion of different levels of maralfalfa (Pennisetum spp.) in rations for guinea pigs on the integrity of the intestinal mucosa was evaluated. For this purpose, 32 weaned type A1 animals were used, randomly distributed in 4 treatments (0, 2, 16, 31% of maralfalfa), with 8 repetitions per treatment. The animals received the experimental diets for a period of 15 days, at the end of which they were sacrificed for the taking of histological samples from the middle small intestine (jejunum) of each one. The samples were processed and stained with the hematoxylin and eosin technique. The following variables were measured: hair length; crypt depth; villus length/crypt depth ratio; villous epithelium height; y, width of muscular tunic. The diet with 31% maralfalfa produced a greater ratio of crypt length/crypt depth and length of the intestinal villi, compared to those obtained with the diets of levels 0, 2, 16%. It is concluded that the inclusion of high levels of fiber sources in the food rations for guinea pigs favors the growth of the intestinal mucosa in the post-weaning phase. Keywords: Guinea pigs, diet, intestinal mucosa, villus, crypt, feeding